Low-dose oncolytic adenovirus therapy overcomes tumor-induced immune suppression and sensitizes intracranial gliomas to anti-PD-1 therapy - Belcaid, Zineb (Neurooncol Adv, 2020)
BACKGROUND: The tumor-selective human adenovirus Delta24-RGD is currently under investigation in phase II clinical trials for patients with recurrent glioblastoma (GBM). To improve treatments for patients with GBM, we explored the potential of combining Delta24-RGD with antibodies targeting immune checkpoints. METHODS: C57BL/6 mice were intracranially injected with GL261 cells and treated with a low dose of Delta24-RGD virus. The expression dynamics of 10 co-signaling molecules known to affect immune activity was assessed in tumor-infiltrating immune cells by flow cytometry after viral injection. The antitumor activity was measured by tumor cell killing and IFNγ production in co-cultures. Efficacy of the combination viro-immunotherapy was tested in vitro and in the GL261 and CT2A orthotopic mouse GBM models. Patient-derived GBM cell cultures were treated with Delta24-RGD to assess changes in PD-L1 expression induced by virus infection. RESULTS: Delta24-RGD therapy increased intratumoral CD8(+) T cells expressing Inducible T-cell co-stimulator (ICOS) and PD-1. Functionality assays confirmed a significant positive correlation between tumor cell lysis and IFNγ production in ex vivo cultures (Spearman r = 0.9524; P < .01). Co-cultures significantly increased IFNγ production upon treatment with PD-1 blocking antibodies. In vivo, combination therapy with low-dose Delta24-RGD and anti-PD-1 antibodies significantly improved outcome compared to single-agent therapy in both syngeneic mouse glioma models and increased PD-1(+) tumor-infiltrating CD8(+) T cells. Delta24-RGD infection induced tumor-specific changes in PD-L1 expression in primary GBM cell cultures. CONCLUSIONS: This study demonstrates the potential of using low-dose Delta24-RGD therapy to sensitize glioma for combination with anti-PD-1 antibody therapy.